2005
DOI: 10.1007/s00429-005-0037-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional clusters in the human parietal cortex as revealed by an observer-independent meta-analysis of functional activation studies

Abstract: The human parietal cortex is a highly differentiated structure consisting of cytoarchitectonically defined subareas that are specifically connected with other cortical and subcortical areas. Based on evidence from neurophysiological studies in subhuman primates these subareas are supposed to be functionally highly specialized. Here, we reviewed 51 different neuroimaging studies on healthy subjects with activation of the parietal lobe in statistical parametric maps. Running a cluster analysis on the stereotacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 65 publications
3
19
0
Order By: Relevance
“…The apraxia after left parietal damage is often present when using either hand (Alexander et al, 1992;Haaland and Harrington, 1996;Leiguarda and Marsden, 2000;Halsband et al, 2001). Additionally, our results seem to be consistent with a meta-analysis of parietal activation studies (Nickel and Seitz, 2005), which suggests that the left IPL is involved in the handobject interaction, and with Heilman et al (1982), who, based on an analysis of human lesion data, suggested that the inferior parietal lobule (supramarginal gyrus) contains visuokinesthetic representations (i.e., perceptual representations related to the motor performances with objects and tools). The clinical observation that apraxia often coexists with aphasia (De Renzi et al, 1980;Haaland and Flaherty, 1984;Kertesz et al, 1984;Papagno et al, 1993) may reflect that both hand-object interaction and language (Binder et al, 1997;Vikingstad et al, 2000) are lateralized to the left hemisphere.…”
Section: Dominance Of the Left Hemisphere For The Sensation Of Hand-osupporting
confidence: 90%
“…The apraxia after left parietal damage is often present when using either hand (Alexander et al, 1992;Haaland and Harrington, 1996;Leiguarda and Marsden, 2000;Halsband et al, 2001). Additionally, our results seem to be consistent with a meta-analysis of parietal activation studies (Nickel and Seitz, 2005), which suggests that the left IPL is involved in the handobject interaction, and with Heilman et al (1982), who, based on an analysis of human lesion data, suggested that the inferior parietal lobule (supramarginal gyrus) contains visuokinesthetic representations (i.e., perceptual representations related to the motor performances with objects and tools). The clinical observation that apraxia often coexists with aphasia (De Renzi et al, 1980;Haaland and Flaherty, 1984;Kertesz et al, 1984;Papagno et al, 1993) may reflect that both hand-object interaction and language (Binder et al, 1997;Vikingstad et al, 2000) are lateralized to the left hemisphere.…”
Section: Dominance Of the Left Hemisphere For The Sensation Of Hand-osupporting
confidence: 90%
“…These two suggestions are consistent with the literature. The superior PPC has been shown to be involved in reconfiguring and updating task-set information immediately following a switch in task (Braver et al, 2003) as well as in shifting attention (Andersen and Buneo, 2002;Behrmann et al, 2004;Cavanna and Trimble, 2006;Corbetta and Shulman, 2002), whereas a recent meta-analysis showed consistent right inferior parietal lobule involvement in tasks of working memory and sustained attention (Nickel and Seitz, 2005). The positive correlation between late cue-locked differential positivity and PPC activation is therefore consistent with our argument that, given an informative cue and sufficient time to prepare, C-R rules can be activated prior to stimulus onset.…”
Section: Informatively Cued Switch N Repeat Contrastmentioning
confidence: 97%
“…This large variability in the AG may potentially reflect the existence of multiple subdivisions within the AG. Indeed, an increasing literature has defined the AG as an aggregate of multiple subdivisions where each subdivision can be characterized by specific functional and connectivity patterns (e.g., Andrews-Hanna and others 2010; Bahnemann and others 2010; Brownsett and Wise 2010; Caspers and others 2008; Eidelberg and Galaburda 1984; Kim 2010; Mars and others 2011; Naidich and others 1995; Nelson and others 2010; Nickel and Seitz 2005; Price GR and Ansari 2011; Rushworth and others 2006; Seghier and others 2010; Seghier and Price 2009; Sharp and others 2010; Uddin and others 2010; Vandenberghe and Gillebert 2009; Yeo and others 2011). This literature has provided an interesting framework for reporting and interpreting AG activations with greater definition, where each subdivision is allowed to have distinct contributions in a given task.…”
Section: Multiple Subdivisionsmentioning
confidence: 99%